ELIMINATING SEGREGATION IN SHARON M. DRAPER’S NOVEL “STELLA BY STARLIGHT” (2015) - Suci Mei Khelly; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2019)
The purpose of this analysis is to expose the issue of eliminating segregation which is done by an 11-year-old girl and to know the contribution of the setting, plot and character in revealing the eliminating segregation. This analysis is related to the concept of life instincts by Sigmund Freud, the concept of self-determination by Ryan and Deci, that is supported by the text and context based interpretation. The result of this analysis shows the protagonist to eliminate the segregation by changing mindset and having good behaviour.